2014
DOI: 10.1001/jamadermatol.2013.7452
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Survival in Patients With Primary Cutaneous Diffuse Large B-Cell Lymphoma, Leg Type, in France

Abstract: A major improvement in the survival of patients with PCDLBCL-LT has occurred over time in France, mainly as a result of the use of intensive rituximab-PCT regimens in most patients, including very elderly ones. Until further prospective clinical trials are conducted, such regimens should be considered as the standard of care in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 24 publications
1
74
0
6
Order By: Relevance
“…Unlike the indolent cutaneous MZL and follicle center lymphomas, primary cutaneous DLBCL, leg-type (PCDLBCL-LT) is aggressive, although rituximab has significantly improved survival outcomes [114, 115]. It classically, though not exclusively, presents as rapidly growing tumors on the legs of women over age 60 [1].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 99%
“…Unlike the indolent cutaneous MZL and follicle center lymphomas, primary cutaneous DLBCL, leg-type (PCDLBCL-LT) is aggressive, although rituximab has significantly improved survival outcomes [114, 115]. It classically, though not exclusively, presents as rapidly growing tumors on the legs of women over age 60 [1].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 99%
“…Localisation on the leg was identified as an independent factor associated with a poor prognosis . In contrast, PCLBCLs‐LT have an aggressive course, requiring a combination of rituximab and polychemotherapy as first‐line treatment …”
Section: Introductionmentioning
confidence: 99%
“…3 In contrast, PCLBCLs-LT have an aggressive course, requiring a combination of rituximab and polychemotherapy as first-line treatment. 7 The information used to make the diagnosis includes morphology, phenotype, and, when available, some molecular features. According to the WHO classification, the tumour cytology and growth pattern may discriminate PCFCLs-LC (classified in the group of PCFCLs whatever the number of large cells) and PCLBCLs-LT. Immunolabelling for bcl-2, MUM1, FOXP1, CD10, bcl-6, CD21 (follicular dendritic cell meshwork) and Ki67 may help to differentiate PCFCLs from PCLBCLs-LT. 8 IgM expression also favours PCLBCL-LT. 9,10 Robson et al suggested that p63 expression is specific to PCLBCL-LT. 11 Our group showed that the MYD88 L265P mutation is a valuable criterion for PCLBCL-LT diagnosis, as it is absent in PCFCLs-LC.…”
Section: Introductionmentioning
confidence: 99%
“…Grange ve ark ise primer kutanöz diffüz geniş B-hücreli lenfomalı hastalarda rituksimab tedavisiyle hayatta kalım oranlarını değerlendirdikleri 115 hastalı bir çalışma planlamışlardır. Rituksimab ve polikemoterapiyi birlikte alan hastalarda 3 ve 5 yıllık hayatta kalım oranlarını %80 ve %74 oranında saptarken, daha az yoğun tedavi alanlarda %48-%38 oranında hayatta kalım tespit edilmiştir (24). Valencak ve ark 16 kutanöz B hücreli lenfoma hastasında rituksimabı monoterapi olarak kullandığında 14 hastada tam remisyon gözlemiştir (48).…”
Section: A-primer Kutanöz B Hücreli Lenfoma Ve Diğer Lenfomalarunclassified